Analisis Kesantunan Berbahasa Guru dan Siswa Dalam Presentasi Pembelajaran Bahasa Indonesia di Kelas VIII SMPI Darul Muwahhidin - Parino Parino; Agus Wijaksono; Andi Wapa (Pusat riset dan Inovasi Nasional, 2023)
The form of language impression is the expression of polite and disrespectful language based on communicative or maksim values. This research aims to describe the form of language impression between teachers and students in indonesian language learning presentation activities in grade VIII SMP Islam Darul Muwahhidin Gambangan Bondowoso which numbered 20 people, consisting of 12 female students and 8 male students. This research is a descriptive qualitative study using a case study design that examines the form of teacher and student language. Data collection activities are conducted through observation, documentation studies, and free interviews during the study activities. The data analysis process is carried out through the stages of data reduction, data presentation, and withdrawal of conclusions. Based on observations made, the fact that there are 9 data on speech events that occur from teacher to student, from 9 data 7 data of speech events worth courtesy, and 2 data on speech events worth not being polite; and there are 8 data on speech events that occur from students to teachers, out of 8 data there are 7 data of speech events of polite value, and 1 data of speech events worth not being polite. Based on the results of the study can be concluded that the interaction between teachers and students in the presentation of Indonesian language learning in grade VIII SMP Islam Darul Muwahhidin Gambangan Bondowoso uses polite language.